Analisis Kualitas Pelayanan UGD Puskesmas Woha Kabupaten Bima terhadap Pengguna Kartu BPJS - Nurmiftahul Abrar; Gery Katon Mahendra (P3M STISIPOL Dharma Wacana Metro, 2022)
The purpose of this study was to determine the service quality of the Woha Health Center Emergency Unit, Bima Regency for BPJS Card users. by using the mix method. The results of the research on the quality of the services of the Emergency Unit on the results of the research on the quality of the services of the Emergency Unit for BPJS card users at the Woha Health Center, Bima Regency,